Interventions delivered in secondary or tertiary medical care settings to improve routine vaccination uptake in children and young people: a scoping review protocol. Issue 7 (3rd July 2020) - Edge, Rhiannon; Isba, Rachel
ABSTRACT: Objective: The objective of this review is to identify and collate the available evidence, and to produce an overview of interventions delivered in secondary and tertiary healthcare settings with the aim of improving vaccination uptake in children and young people. Introduction: Vaccine hesitancy appears in the World Health Organization's Ten Threats to Global Health in 2019. 1 Time spent in secondary or tertiary healthcare settings with a child or young person may present an opportunity to deliver vaccination-focused interventions. National Institute for Health and Care Excellence guidance highlights a gap in the evidence of the effectiveness of different interventions aimed at increasing immunization uptake among children and young people. 2 Inclusion criteria: Quantitative studies that describe interventions delivered in secondary and tertiary care settings will be included. Participants will include children and young people aged less than 16 years and/or their parents/carers (potentially interventions could be delivered to the child-parent/carer dyad) present in a secondary or tertiary care setting as either a patient or relative. Methods: This scoping review will be conducted using MEDLINE, CINAHL, Cochrane Library, Embase, Web of Science, as well as gray literature. The scoping review will exclude publications not available in English and any publication older than 30 years. Two reviewers will independently select articles using the inclusion criteria, based on their title and abstract. Data will be extracted from selected full text articles using a data extraction tool based on JBI recommendations. Study findings will be presented in tabular form detailing the interventions identified in the literature.